The communication of a secondary care diagnosis of autoimmune hepatitis to primary care practitioners: a population-based study - Varyani, Fumi; Card, Timothy R.; Kaye, Philip; Aithal, Guru P.; West, Joe (BioMed Central, 2013)
Background Autoimmune Hepatitis is a chronic liver disease which affects young people and can result in liver failure leading to death or transplantation yet there is a lack of information on the incidence and prevalence of this disease and its natural history in the UK. A means of obtaining this information is via the use of clinical databases formed of electronic primary care records. How reliably the diagnosis is coded in such records is however unknown. The aim of this study therefore was to assess the proportion of consultant hepatologist diagnoses of Autoimmune Hepatitis which were accurately recorded in General Practice computerised records.